Adulteration of cow's milk with buffalo's milk detected by an on-site carbon nanoparticles-based lateral flow immunoassay. (30th July 2021) - Sharma, Rajan; Verma, Archana; Shinde, Nitin; Mann, Bimlesh; Gandhi, Kamal; Wichers, Jan H.; van Amerongen, Aart
Highlights: A competitive rapid lateral flow immunoassay detects buffalo's milk in cow's milk. Buffalo's milk specific proteins were isolated for raising polyclonal antibodies. Amorphous carbon nanoparticles were employed as a label. The sensitivity of the test is below 1% adulteration. Full competition, i.e. no visible test line, is reached at 5%. Abstract: A competitive lateral flow immunoassay using amorphous carbon nanoparticles (CNPs) and non-immunoglobulin antigen has been developed for the rapid detection of adulteration of cow's milk with buffalo's milk. Purified polyclonal antibodies against a specific buffalo's milk protein fraction were conjugated to CNPs and sprayed on a conjugate pad. The test line consisted of buffalo's skimmed milk proteins (1.6 μg/cm), while the control line contained anti-rabbit antibodies raised in goat (0.5 μg/cm). In the test procedure milk sample is mixed with 100 mM borate buffer (pH 8.8 containing 1% BSA and 0.05% Tween 20) and pipetted onto the sample-cum-conjugate pad. A black/grey test line can be observed if the sample is free from buffalo's milk. The sensitivity of the test i.e. no visible test line is 5% adulteration of cow's milk with buffalo's milk. The test has applicability at the milk receiving stations and can be applied to heated milk samples.